Variation in dietary salt intake induces coordinated dynamics of monocyte subsets and monocyte-platelet aggregates in humans: implications in end organ inflammation. - Xin Zhou (PLoS ONE, 2013)
BACKGROUND: Monocyte activation and tissue infiltration are quantitatively associated with high-salt intake induced target organ inflammation. We hypothesized that high-salt challenge would induce the expansion of CD14++CD16+ monocytes, one of the three monocyte subsets with a pro-inflammatory phenotype, that is associated with target organ inflammation in humans. METHODOLOGY/PRINCIPAL FINDINGS: A dietary intervention study was performed in 20 healthy volunteers, starting with a 3-day usual diet and followed with a 7-day high-salt diet (≥15 g NaCl/day), and a 7-day low-salt diet (≤5 g NaCl/day). The amounts of three monocyte subsets ("classical" CD14++CD16-, "intermediate" CD14++CD16+ and "non-classical" CD14+CD16++) and their associations with monocyte-platelet aggregates (MPAs) were measured by flow cytometry. Blood oxygen level-dependent magnetic resonance imaging (BOLD-MRI) was used to evaluate renal hypoxia. Switching to a high-salt diet resulted in CD14++ monocyte activation and a rapid expansion of CD14++CD16+ subset and MPAs, with a reciprocal decrease in the percentages of CD14++CD16- and CD14+CD16++ subsets. In vitro study using purified CD14++ monocytes revealed that elevation in extracellular [Na(+)] could lead to CD14++CD16+ expansion via a ROS dependent manner. In addition, high-salt intake was associated with progressive hypoxia in the renal medulla (increased R2* signal) and enhanced urinary monocyte chemoattractant protein-1 (MCP-1) excretion, indicating a temporal and spatial correlation between CD14++CD16+ subset and renal inflammation. The above changes could be completely reversed by a low-salt diet, whereas blood pressure levels remained unchanged during dietary intervention. CONCLUSIONS/SIGNIFICANCE: The present work demonstrates that short-term increases in dietary salt intake could induce the expansion of CD14++CD16+ monocytes, as well as an elevation of MPAs, which might be the underlying cellular basis of high-salt induced end organ inflammation and potential thromboembolic risk. In addition, this process seems largely unrelated to changes in blood pressure levels. This finding provides novel links between dietary salt intake, innate immunity and end organ inflammation.